Contribution of Fisheries and Aquaculture to Food Security and Poverty Reduction: Assessing the Current Evidence. (March 2016) - Béné, Christophe; Arthur, Robert; Norbury, Hannah; Allison, Edward H.; Beveridge, Malcolm; Bush, Simon; Campling, Liam; Leschen, Will; Little, David; Squires, Dale; Thilsted, Shakuntala H.; Troell, Max; et al.
Highlights: We assess the contribution of fish-related activities to food security and poverty reduction. A scoping review on more than 200 articles grouped into relevant themes is completed. The review reveals a heterogeneous "landscape" in terms of scientific quality and methodological rigor. The contribution of fisheries and aquaculture to food security or economic development at global or macro-levels remains debated. Evidence/science and policy narratives and action are often disconnected. Summary: Following a precise evaluation protocol that was applied to a pool of 202 articles published between 2003 and 2014, this paper evaluates the existing evidence of how and to what extent capture fisheries and aquaculture contribute to improving nutrition, food security, and economic growth in developing and emergent countries. In doing so we evaluate the quality and scientific rigor of that evidence, identify the key conclusions that emerge from the literature, and assess whether these conclusions are consistent across the sources. The results of the assessment show that while some specific topics are consistently and rigorously documented, thus substantiating some of the claims found in the literature, other areas of research still lack the level of disaggregated data or an appropriate methodology to reach consistency and robust conclusions. More specifically, the analysis reveals that while fish contributes undeniably to nutrition and food security, the links between fisheries/aquaculture and poverty alleviation are complex and still unclear. In particular national and household level studies on fisheries' contributions to poverty alleviation lack good conceptual models and produce inconsistent results. For aquaculture, national and household studies tend to focus on export value chains and use diverse approaches. They suggest some degree of poverty alleviation and possibly other positive outcomes for adopters, but these outcomes also depend on the small-scale farming contexts and on whether adoption was emergent or due to development assistance interventions. Impacts of fish trade on food security and poverty alleviation are ambiguous and confounded by a focus on international trade and a lack of consistent methods. The influences of major drivers (decentralization, climate change, demographic transition) are still insufficiently documented and therefore poorly understood. Finally the evaluation reveals that evidence-based research and policy narratives are often disconnected, with some of the strongest and long-lasting policy narratives lacking any strong and rigorous evidence-based validation. Building on these different results, this paper identifies six key gaps facing policy-makers, development practitioners, and researchers.